The Impact of Reward System on Job Satisfaction and In-role Performance among Lecturers in Indonesia - Fadhil, Muhammad (Faculty of Economics, Universitas Negeri Indonesia,Indonesia, 2023)
The current study attempts to analyze the effect of the reward system (intrinsic and extrinsic) on job satisfaction and in-role performance. Moreover, the expected effect of job satisfaction and in-role performance was also tested. This research focuses on all permanent lecturers at private universities in Makassar under the Institute for Higher Education Services Region IX (LLDIKTI IX). Self-administered online questionnaires were designed and distributed to respondents who met the judgment sampling criteria. The 220 respondents were determined as primary data and then tested with structural equation modeling (SEM) analysis based on partial least squares (PLS). The founding statistically stated that intrinsic rewards positively and significantly affect lecturer in-role performance and job satisfaction. Extrinsic rewards have a significant effect on in-role performance but are not significant on lecturer job satisfaction. Furthermore, the mutual relationship between in-role performance-job satisfaction was confirmed and supported. These findings provide the latest insights into productive human resource planning strategies in higher education in Indonesia.